Rapid quantitative analysis of palladium in ores using laser-induced breakdown spectroscopy assisted with laser-induced fluorescence (LIBS-LIF). Issue 12 (21st October 2022) - Elhamdaoui, Ismail; Mohamed, Nessrine; Selmani, Samira; Bouchard, Paul; Sabsabi, Mohamad; Constantin, Marc; Vidal, François
Abstract : This paper discusses the use of conventional LIBS and LIBS-LIF techniques for measuring trace amounts of palladium in solid ore samples. Abstract : This paper discusses the use of conventional LIBS and LIBS-LIF techniques to measure trace amounts of palladium in solid ore samples. Combination of excitation/fluorescence of Pd lines as well as plasma creation conditions were studied to optimize the performances of LIBS-LIF for spectrochemical analysis of palladium. Calibration curves were established using pressed powder pellets of reference materials doped with a solution of palladium. The optimum single-shot limit of detection (LoD) of palladium obtained by the conventional LIBS technique for our setup (Pd 348.12 nm line) was 10 ppm or 1 ppm using 100 laser shots. In contrast, LIBS-LIF (Pd 276.31 nm line for excitation and Pd 351.69 nm line for fluorescence) gave an LoD of 160 ppb for a single laser shot or 16 ppb using 100 laser shots. In addition, LIBS-LIF can resolve the palladium spectral lines in iron-bearing mineral matrices, which is problematic with conventional LIBS due to spectral interference. It is demonstrated for the first time that LIBS-LIF could enable the mining industry to rapidly measure trace amounts of palladium at sub-ppm levels per laser shot in solid ore samples without any sample preparation. The obtained results are a proof of concept of the LIBS-LIF technique feasibility for the quantitative analysis of palladium in ore samples. They show that LIBS-LIF could be a good candidate for real time analysis of palladium in ore samples in terms of standoff capabilities, sensitivity and speed of analysis.